People's Republic of China Financial Sector Assessment Program : CPSS-IOSCO Recommendations for Securities Settlement Systems and Central Counterparties - World Bank; International Monetary Fund (World Bank, Washington, DC, 2017)
The Securities Settlement Systems (SSS) in the People's Republic of China (PRC) are organized around three different types of markets, which are the bond market, the corporate securities market, and the futures market. The China Government Depositary and Clearing Corporation Limited (CCDC) is the SSS as well as the central securities depository (CSD) for bonds. The China Securities Depository and Clearing Corporation Limited (SD and C) is the central counterparty (CCP), SSS, as well as the CSD for all instruments traded on the Shanghai Stock Exchange (SSE) and Shenzhen Stock Exchange (SZSE). The four futures exchanges have their own clearing and settlement departments, which offer the function of a CCP. The CCDC, SD and C, and Shanghai Futures Exchange (SHFE), Dalian Commodities Exchange (DCE), and Zhengzhou Commodities Exchange (ZCE) operate important securities and derivatives settlement systems both, due to the large volume and value of transactions and the fact that they support key financial sector markets (interbank bond market, stock exchanges and futures). The assessment of the bonds market-CCDC system against the Recommendations for Securities Settlement Systems (RSSS) concludes that the system observes (observed or broadly observed) thirteen of the 19 recommendations, being one not applicable. The assessment of the stock exchanges-SD and C system against the RSSS concludes that the system observes (observed or broadly observed) seventeen of the 19 recommendations. The assessment of the commodities futures markets-SHFE system against the Recommendations for Central Counterparties (RCCP) concludes that the system observes (observed or broadly observed) eleven of the 15 recommendations, being one not applicable. The present document is the assessment of securities and derivatives settlement systems in the PRC based on the recommendations of the Committee on Payment and Settlement Systems (CPSS) and the International Organization of Securities Commissions (IOSCO) for RSSS and the recommendations of CPSS-IOSCO for Central Counterparties (RCCP). The paper is divided into following five parts: the first part gives general information; the second gives information and methodology used for assessment; the third part is securities and derivatives settlement systems infrastructure overview; the fourth part is main findings from the assessment with international standards; and the fifth part gives authorities' response.